2009
DOI: 10.1039/b909866f
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic dehydrative etherification and chlorination of benzyl alcohols in ionic liquids

Abstract: Dibenzyl ethers and benzyl chloride can be obtained in moderate to excellent yields through Pd-catalysed reactions in hydrophobic ionic liquids using microwave or conventional heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
14
1
1
Order By: Relevance
“…During our study of etherification reactions in ILs, 20 upon changing the IL from those containing imidazolium cations to [P 66614 ]DBS (DBS = dodecylbenzenesulfonate) we discovered that the Pd(II)-IL mixtures would change colour over time in the absence of any reagents. We sought to discover the origin of this colour change.…”
Section: Preliminary Investigationsmentioning
confidence: 99%
“…During our study of etherification reactions in ILs, 20 upon changing the IL from those containing imidazolium cations to [P 66614 ]DBS (DBS = dodecylbenzenesulfonate) we discovered that the Pd(II)-IL mixtures would change colour over time in the absence of any reagents. We sought to discover the origin of this colour change.…”
Section: Preliminary Investigationsmentioning
confidence: 99%
“…In our previous studies, very low conversions were observed in the absence of palladium for dehydrative etherification reactions in imidazolium ionic liquids,5 however, we have since discovered that the reaction can be performed without any metal catalyst in phosphonium ionic liquids (Scheme ). Furthermore, [BMIm]PF 6 was not completely stable under the reaction conditions, as HF was released via hydrolysis of the ionic liquid and our initial studies showed greater stability for phosphonium ionic liquids.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, imidazolium ionic liquids have acted as both catalyst and solvent 24. Previously, we reported dehydrative etherifications of benzylic alcohols in imidazolium ionic liquids, specifically, [BMIm]PF 6 (1‐butyl‐3‐methylimidazolium hexafluorophosphate) in the presence of Pd catalysts 5. We chose to study such reactions in ionic liquids because these solvents display an exceptional ability to stabilize ionic intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kerton et al reported the procedure based on the utilization of Pd(CH 3 CN) 2 Cl 2 for the etherification of benzyl alcohol in hydrophobic ionic liquids (1-Butyl-3-methylimidazolium hexafluorophosphate, [BMIM]PF 6 ) using a microwave or conventional heating. 147 In the presence of NH 4 Cl chlorination of benzyl alcohol occurred. Palladium on magnesium oxide (Pd/MgO) catalyzed the formation of thioethers from thiols and aldehydes formed in situ from the alcohol by means of a "borrowing hydrogen" method.…”
mentioning
confidence: 99%